The effects of strength training on distance running performance and running injury prevention - Karp, J. R. (Journal of Physical Education and Sport, 2024)
Introduction: From recreational to elite runners, strength training has become a popular addition to distance running training programs to improve performance and prevent running-related injuries. However, some incompatibilities exist between aerobic endurance training and strength training, including muscle hypertrophy and mitochondrial and capillary densities. Although our knowledge of the independent effects of aerobic endurance training and strength training dates back a long time, our knowledge of the effects of strength training on aerobic endurance performance is still young. Purpose: To bring greater clarity to the subject of strength training for distance running performance and running injury prevention to runners, coaches, clinical practitioners, and the scientific community, this comprehensive literature review offers a critical narrative summary of the research on strength training and distance running performance and running injury prevention and includes several important directions for future research. Methods: All English-language published studies on the effects of strength training on distance running performance and the effects of strength training on distance running injury prevention were found using PubMed and Google Scholar databases. All studies were eligible for selection, as long as the intervention included some type of strength training using various loads and reps/sets combinations and the dependent variable was either running performance, physiological factors related to running performance, or the prevalence of distance running-related injury. Results and Conclusions: Strength training, either with heavy loads (= 90% 1-rep max) or with explosive movements, has been shown to have a small, positive effect on running economy, laboratory measures of performance (e.g., maximal aerobic speed, time to exhaustion), and running time-trial performance over distances from 3 to 10 kilometers. However, strength training has not been found to improve other aerobic physiological factors related to distance running performance, including VO2max and lactate threshold. Furthermore, no studies have examined the effect of strength training on real-life distance running race performance or on long-distance running performance (e.g., marathon, half-marathon). Regarding running-related injuries, muscle weakness, especially of the hip, seems to be a characteristic of injured runners in both retrospective and prospective studies; however, the evidence is lacking that muscle weakness is a cause of running injuries and is equivocal that strength training prevents running injuries, with studies limited to novice or recreational runners.